REMOVAL OF HEAVY METALS USING MAGNIFERA INDICA FROM DYEING EFFLUENT - Raj, I.R.Ifer; Udhayan, C. (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
Colour is the main attraction of any fabric. Manufacture and use ofsynthetic dyes from fabric dyeing as therefore become a massive industry today. Use ofsynthetic dyes has an adverse effect on all forms of life. Presence of sulphur naphthol, vatdyes, nitrates, acetic acids, soaps, enzymes, chromium compounds and heavy metals likecopper, arsenic, lead, cadmium, mercury, nickel, and cobalt and certain auxiliarychemicals all collectively make the textile effluent highly toxic. It is important to removethese pollutants from the waste water before their final disposal. The study wasperformed to investigate the concentration of toxic heavy metals like cadmium (Cd) andZinc (Zn). It was observed that the concentration of cadmium were much higher than themaximum permissible limits. Process parameters which include adsorbent dosages, PHand contact time of solution were varied in order to evaluate their influence on theadsorption process. The optimum contact time, dosage and PH for carbon with I.R-0.75was 90 mins, 200mg and 7.00 with removal efficiency of 99.69%, 98.55% and 93.71%respectively. Hence easy and effective techniques are required for fine tuning of wastewater treatment.